"WASTE-FREE SCHOOLS: STRATEGIES FOR BUILDING ENVIRONMENTAL AWARENESS IN HIGH SCHOOLS" - Nayla Nurul Afifah; Sulaiman Zuhdi; Wisaam Addar Hasan Pasaribu; Muhammad Zaidan Alawi; Raihan Fadhil Aiman Sadikin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Summary Waste management in schools is an important step in supporting environmental sustainability. This article examines the implementation of the Zero Waste Schools program in Indonesia with a focus on the application of the Reduce, Reuse, Recycle (3R) principle to reduce waste. Although there are clear positive impacts, challenges such as lack of facilities and awareness among students and teachers still hinder the success of the program. This article provides recommendations for integrating waste management into the school curriculum, providing adequate facilities and increasing school community participation. Schools are expected to become agents of change by increasing environmental awareness and creating a cleaner and more sustainable environment.